Investigation of a Novel PLGA/CaP Scaffold in the Healing of Tooth Extraction Sockets to Alveolar Bone Preservation in Humans - Araujo-Pires, Ana Claudia; Mendes, Vanessa Cristina; Ferreira-Junior, Osny; Perri Carvalho, Paulo Sergio [UNESP]; Guan, Limin; Davies, John Edward (Wiley-Blackwell, 2016)
Background: It is expected that 40% to 60% of initial alveolar bone volume will be lost up to 6months after tooth extraction. OsteoScafTM (TRT, Toronto, ON, Canada) (poly (DL-lactide-co-glycololide/calcium phosphate [PLGA/CaP] scaffold) is a novel bone substitute material and represents a promising alternative for maintaining alveolar bone integrity in this clinical scenario. Purpose: Here it was hypothesized that OsteoScaf would reduce alveolar bone lost after tooth extraction in patient, acting as a clot-retention device. Material and Methods: A total of 10 patients (32 sockets) were included in the study, of which 16 sockets were grafted with OsteoScaf and 16 were used as control (coagulum alone). Cone beam computed tomography (CBCT) was performed both immediately following extraction and also at 120 days postoperatively, at which time biopsy samples were also harvested for histological analyses. Results: Quantitative analysis of CBCT showed less bone resorption in the OsteoScaf groups, being 10.5% to 14.4% less bone lost in the center of the socket, 15.4% in the buccal region, and 12.6% in the palatal. Qualitative histological analysis showed new bone tissue in direct apposition to the scaffold - demonstrating its osteoconductive nature. Conclusion: OsteoScaf diminished the expected bone lost during the postextraction remodeling of the alveolar bone ridge at 120 days postextraction.
Keywords: alveolar bone remodeling; biomaterials; bone regeneration; bone substitutes; bone tissue engineering; CBCT imaging; clinical study; extraction socket; histological analysis; micro-CT